EFFECTS OF MUCUNA SEED EXTRACT ON SPERM FUNCTIONAL INTEGRITIES AND SEMINAL OXIDATIVE STRESS INDICES OF VITRIFIED GOAT SEMEN - Daramola, James Ola; Oyewusi, Joshua Adeoye; Sorongbe, Taiwo Amidu; Adekunle, Ezekiel Oluwafemi; Iyanda, Olayinka Ayobami; Onanuga, Oluwakemi Dayo; Olayemi, Folarin Daniel; Falujo, Femi Damilola; Tanimowo, Lateef Semako; Omyema, Prisca Onyinyechi; Sobowale, Omobolanle Abibat; Sodiya, Olorunjuda O; et al. (Journal of Agricultural Sciences (Belgrade), 2017)
Effects of mucuna seed extract (MSE) in tris-extenders on sperm functional integrities and seminal oxidative stress indices of vitrified spermatozoa obtained from West African Dwarf (WAD) goat bucks were evaluated. Semen samples were diluted with varying levels (0, 0.25, 0.5, 0.75, 1 g/100 mL of diluent) of MSE in tris-extenders. Diluted semen samples were vitrified and preserved in liquid nitrogen. The results showed that sperm functional integrities (acrosome and membrane integrities) in extenders supplemented with MSE were comparable. However, seminal oxidative stress indices (Malondialdehyde [MDA] and acrosin activity differed (P<0.05) among the various treatments and the control. The results showed that semen vitrified with MSE had reduced (P<0.05) MDA concentrations compared to the control. Higher (P<0.05) acrosin activities were observed in semen vitrified with MSE compared to the control except at 0.25g MSE and optimal values were recorded at 1g MSE. The findings indicated that MSE in the tris-extenders reduced MDA concentration with congruent elevated acrosin activity and consequently maintained sperm functional integrities of vitrified spermatozoa of the WAD goat.